The Instagram Aesthetic: Exploring the relationship between colour and consumer engagement amongst social media's beauty brands - Flower, Rachel (2020)
Literature within colour psychology has shown how colour has the power to elicit a range of affective responses and emotion in consumers. Marketing applications typically focus on how colour can influence responses to advertisements, products and e-commerce sites. However, marketing scholars are yet to thoroughly investigate how colour theories manifest on social media. This paper explores the relationship between colour and consumer engagement on Instagram - one of the most popular social networking platforms. It samples a total of 200 images from the top 10 beauty brands on the platform, alongside two behavioural metrics (likes and comments). The results identify four colours occurring most frequently within the sample: rose/beige, livid brown/black, whisper/pink-grey and au chico/red-brown. Rose/beige represents the highest number of likes, and livid brown represents the highest number of comments. The analysis failed to find a statistically significant relationship between the four colours, as a whole, and the engagement behaviours. However, the results indicate that individual colours, rose/beige and whisper/pink-grey, do have a statistically significant relationship to both liking and commenting behaviours. Overall, the colour associated with the highest consumer engagement was rose/beige. These findings do bear similarity to studies on Facebook and Pinterest, which also assessed the impact of colour on social media engagement (Zailskaitė-Jakštė et al 2017; Bakhshi and Gilbert, 2015). This paper is one of the few to explore whether certain colours trigger different types of social media engagement, whilst attempting to establish a connection between colour theory and the motivation behind liking and commenting behaviours. To the best of our knowledge this study is also the first of its kind to sample exclusively from one industry, beginning to evaluate the role of business context. Conclusions discuss the contributions of the study, the managerial implications and the numerous avenues for future research.